2020
DOI: 10.3389/fpsyg.2020.570435
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Impact of the Civil War and COVID-19 on Libyan Medical Students: A Cross-Sectional Study

Abstract: Objective: We aim to determine the psychological status of medical students during the COVID-19 outbreak and civil war in Libya. Methods: A cross-sectional study was conducted among medical students from 15 medical schools between April 20 and May 1, 2020. The demographic characteristics, generalized anxiety disorder 7-item (GAD-7) scale, and patient health questionnaire (PHQ-9) results were collected. Results: Of the 3,500 students, 2,430 completed the survey. The mean (± SD) score of anxiety symptoms determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
5
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 55 publications
2
58
5
5
Order By: Relevance
“…At the local level, two independent studies conducted by Hweissa NAB, et al [26] and Elshwekh H, et al [27] found that 79.9% and 89.3% of the surveyed Libyan healthcare workers have adequate knowledge about the COVID-19, respectively. Elhadi M, et al [28] surveyed 3,669 medical and non-medical students from fifteen universities in Libya. The authors found that 71.8% had adequate knowledge accompanied by a positive attitude and professional behavior towards COVID-19.…”
Section: Current Situation Of Covid 19mentioning
confidence: 99%
“…At the local level, two independent studies conducted by Hweissa NAB, et al [26] and Elshwekh H, et al [27] found that 79.9% and 89.3% of the surveyed Libyan healthcare workers have adequate knowledge about the COVID-19, respectively. Elhadi M, et al [28] surveyed 3,669 medical and non-medical students from fifteen universities in Libya. The authors found that 71.8% had adequate knowledge accompanied by a positive attitude and professional behavior towards COVID-19.…”
Section: Current Situation Of Covid 19mentioning
confidence: 99%
“…We excluded 63 articles and therefore retrieved and appraised the 20 lasting articles based on their full-texts and also considering our selection criteria. Finally, 12 articles [24][25][26][27][28][29][30][31][32][33][34][35] were systematically reviewed and qualitatively summarized. The PRISMA flow chart showing our study selection process is shown in figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Amid selected studies, 11 were reported as cross-sectional studies, and one as a transversal descriptive study [33]. Data were collected exclusively electronically (online surveys) in 9/12 studies, only with a paper version form in one study [32], both with online and paper forms in one study [29], and through phone calls in one study [26]. Most of studies (7/12) used a non-probabilistic sampling method, 4 studies reported a probabilistic sampling technique, and one article reported no details on the sampling method used.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations